Broadband Access Technologies Evaluation Tool (BATET) - Pereira, João Paulo Ribeiro; Pires, José Adriano (Technological and Economic Development of Economy, 2007)
The goal of this paper is to identify all the essential costs of building broadband access networks, and then to comparise different technologies in various scenarios. Different market segments (Scenarios) have different geographical characteristics and will require different amounts of access bandwidth. These different market segments will be served by alternative access technologies that minimise overall costs. In order to do this, we have developed a model framework and an evaluation tool. To measure the attractiveness of several broadband access technologies, the proposed tool compares the costs, revenues, NPV, IRR, payback periods etc for 3 scenarios. The paper presents a techno‐economic analysis of 8 broadband technologies for access networks: digital subscriber line (DSL), hybrid fibre coax (HFC), power line communications (PLC), fibre to the home (FTTH), fibre to the curb (FTTC), fibre to the cabinet (FTTCab), and wireless alternatives such as WiMAX and satellite.Plačiajuosčio ryšio technologijų įvertinimo priemonėSantrauka. Šio straipsnio tikslas – nustatyti visas svarbiausias plačiajuosčio ryšio tinklo įrengimo išlaidas ir palyginti įvairius skirtingų technologijų scenarijus. Įvairūs rinkos segmentai (scenarijai) turi skirtingas geografines charakteristikas ir reikalauja skirtingo dydžio ryšio juostos pločio. Šie skirtingi rinkos segmentai bus aptarnaujami alternatyvių ryšio technologijų, kurios minimizuoja bendrąsias sąnaudas. Norint tai atlikti, buvo sukurtas modelis ir įvertinimo priemonė. Siekiant nustatyti keliu plačiajuosčio ryšio technologijų patrauklumą, pasiūlyta priemonė palyginti trijų scenarijų sąnaudas, pajamas, atsipirkimo laiką ir kita. Straipsnyje pateikiama aštuonių plačiajuosčio ryšio technologijų technoekonominė analizė.Reikšminiai žodžiai: ryšio tinklai, plačiajuosčio ryšio technologijos, sanaudu modelis.First Published Online: 21 Oct 2010